Comparison of a nonpneumatic device to four currently available intermittent pneumatic compression devices on common femoral blood flow dynamics - Labropoulos, Nicos; Giuliano, Karen K.; Tafur, Alfonso J.; Caprini, Joseph A. (Journal of vascular surgery. Venous and lymphatic disorders (New York, NY), 2021)
The purpose of the present study was to compare common femoral vein blood flow enhancement during external mechanical compression using the novel, nonpneumatic Recovery Force Health Movement and Compressions (MAC) System (Recovery Force USA, Fishers, Ind), and four currently available intermittent pneumatic compression devices. The MAC device was compared with the Kendall SCD 700 (Cardinal Health, Dublin, Ohio), Arjo Huntleigh Flowtron ACS900 (Arjo, Malmö, Sweden), ActiveCare+S.F.T. (Zimmer Biomet, Warsaw, Ind), and Circul8 (Ortho8, Rocklin, Calif). Doppler ultrasound measurements for each device were directly obtained from the right common femoral vein by a registered vascular technologist. The peak flow velocity and the time taken to reach the peak were calculated. For the MAC system only, the subjects were asked to walk a minimum of 500 steps while wearing the system, which was then checked for slippage. Leg size measurements were obtained using the noncontact Sigvaris Legreader XT5 (Vialis Ortopedia, Turin, Italy). The MAC device is not yet commercially available, and the present study was a prequel to clinical studies of venous thromboembolism prevention. We recruited a broad range of 20 subjects who varied in age (mean ± standard deviation [SD], 50.5 ± 16.2 years), body mass index (mean ± SD, 26 ± 5.5 kg/m2), gender (male, 25%; female, 75%), and right calf circumference (mean ± SD, 37.2 ± 5.5 cm). The peak flow velocity compared with the baseline measurements was significantly greater for the Recovery Force Health MAC System for three (Kendall SCD 700, P = .02; ActiveCare+S.F.T., P = .003; Circul8, P < .001) of the four comparisons. Although the difference was not significant, the Arjo Huntleigh Flowtron ACS900 (SD, 3.4 cm/s) had more measurement variability in the peak flow velocity compared with baseline than did the MAC System (SD, 1.9 cm/s). The MAC had a significantly (P < .001) faster rise time to peak flow compared with the comparison devices. It was the only device to achieve the target peak flow velocity over baseline of at least three times in every body mass index group. Finally, the MAC System met the goal of <2.5 cm of movement after ambulation in 100% of the measurements, with 75% of the measurements showing no movement. The MAC System is a mobile device that remained in place during ambulation and provided more consistent external mechanical compression in the desired range compared with the other three devices included in the present study.